Endovascular treatment of femoro-popliteal disease with the Supera stent: results of a multicenter study - Giuseppe Guzzardi; Angelo Spinazzola; Gianluca Cangiano; Massimiliano Natrella; Andrea Paladini; Carla Porta; Luca Boccalon; Davide Negroni; Giovanni Leati; Domenico Laganà; Riccardo Guglielmi; Alessandro Carriero (SAGE Publishing, 2021)
Background: Even though many types of stents have been tested in superficial femoral artery (SFA) and popliteal artery (PA), the vast majority of these devices have provided an unsatisfactory outcome, probably due their unsuitable anatomical and physiological characteristics. The Supera peripheral stent (Abbott Vascular, Santa Rosa, CA, USA) is a braided interwoven nitinol device specifically designed for treating atherosclerotic lesions of the femoro-popliteal segment. The aim of this multicenter retrospective study was to describe the effectiveness of Supera stents in the management of femoral-popliteal atherosclerotic lesions and to critically analyze our findings in the context of current and past literature. Design and Methods: In this study we enrolled only patients who satisfied the inclusion criteria: 1) patients affected by chronic obstructive arterial disease (COAD) grade II, as per Rutherford classification; 2) patients treated with endovascular revascularization and Supera stent implantation in the femoro-popliteal axis. We retrospectively analyzed the Doppler Ultra-sound (US) follow-up at 12-24 and 36 month in order to detect the vascular occlusions. The primary patency, primary patency assisted and TLR were described statistically analyzed by survival analysis and the demographic data, clinical data, device safety following stenting were described as frequency and mean value. Results: 105 endovascular procedures on 99 patients for femoro-popliteal stenting with Supera were performed in four Italian hospitals. The median follow-up was 39 months (range 6-72), with primary patency rate of 83.1%, 74.3% and 69.5% at 12, 24 and 36 months after the procedure. The primary patency assisted was 89.9%, 76.8% and 73.4% in the same period, while the freedom from TLR values were 92.7%, 91.5% and 89.5% at 12, 24 and 36 months after the procedure, respectively. The mortality rate recorded at 12 months from the Supera implantation was 2.8% (3 out of 99 patients enrolled). Conclusions: Our data were in agreement with the current literature, showing the non-inferiority Supera stent in relation to the other stent available. Supera stent showed an excellent safety, effectiveness profile and high durability for the treatment of PAD patients with femoro-popliteal artery disease.